Nanoscale Mapping of the Conductivity and Interfacial Capacitance of an Electrolyte‐Gated Organic Field‐Effect Transistor under Operation. (25th October 2020) - Kyndiah, Adrica; Checa, Martí; Leonardi, Francesca; Millan‐Solsona, Ruben; Di Muzio, Martina; Tanwar, Shubham; Fumagalli, Laura; Mas‐Torrent, Marta; Gomila, Gabriel
Abstract: Probing nanoscale electrical properties of organic semiconducting materials at the interface with an electrolyte solution under externally applied voltages is key in the field of organic bioelectronics. It is demonstrated that the conductivity and interfacial capacitance of the active channel of an electrolyte‐gated organic field‐effect transistor (EGOFET) under operation can be probed at the nanoscale using scanning dielectric microscopy in force detection mode in liquid environment. Local electrostatic force versus gate voltage transfer characteristics are obtained on the device and correlated with the global current–voltage transfer characteristics of the EGOFET. Nanoscale maps of the conductivity of the semiconducting channel show the dependence of the channel conductivity on the gate voltage and its variation along the channel due to the space charge limited conduction. The maps reveal very small electrical heterogeneities, which correspond to local interfacial capacitance variations due to an ultrathin non‐uniform insulating layer resulting from a phase separation in the organic semiconducting blend. Present results offer insights into the transduction mechanism at the organic semiconductor/electrolyte interfaces at scales down to ≈100 nm, which can bring substantial optimization of organic electronic devices for bioelectronic applications such as electrical recording on excitable cells or label‐free biosensing. Abstract : Nanoscale electrical conductivity and interfacial capacitance maps of an operating electrolyte gated organic field effect transistor are obtained by using scanning dielectric microscopy in‐liquid environment. The conductivity maps reveal the on–off transition of the transistor device, while the interfacial capacitance maps show the minute heterogeneities resulting from phase separtion in the active organic semiconductor material.